Comprehensive Analysis of m6A Regulators Characterized by the Immune Cell Infiltration in Head and Neck Squamous Cell Carcinoma to Aid Immunotherapy and Chemotherapy - Zhiqiang Yang (Frontiers Media S.A., 2021)
BackgroundN6-Methyladenosine (m6A), which is a prevalent regulator of mRNA expression, has gathered increasing study interests. Though the role of m6A as being important in many biological processes (such as growth and proliferation of cancers) has been well documented, its potential role in tumor immune microenvironment (TIME) has rarely been analyzed.MethodsWe downloaded RNA expression, single nucleotide polymorphism (SNP), and copy number variation (CNV) data from The Cancer Genome Atlas (TCGA). We then curated 21 m6A regulators and clustered patients into three m6A subtypes and m6A-related gene subtypes and compared them based on overall survival (OS). The combination of CIBERSORT as well as ssGSEA quantified the infiltration levels of immune cells and immune-related functions. The m6A scores were determined by using principal component analysis (PCA) algorithm. Furthermore, we evaluate the correlation of m6A regulators with immune and response to therapy.ResultsThree m6A clusters were identified based on the TCGA-HNSCC cohort, and there were significant associations among them in overall outcomes and caner-related pathways. We found that three m6A clusters were consistent with three phenotypes: immune-inflamed, immune-dessert, and immune-excluded. HNSCC patients were divided into high– and low–m6A score groups based on the cutoff of m6A score. Patients with lower m6A score had better overall survival outcome. Further analysis indicated that patients with higher m6A score presented higher tumor mutation burden (TMB). In addition, patients in low–m6A score subgroup had high chemotherapeutics sensitivity. GEO cohort confirmed patients with low m6A score demonstrated significant overall survival advantages and clinical benefits. Low m6A score carry an increased neoantigen load, eliciting a response to immunotherapy, and its value in predicting survival outcomes of immunotherapy was also confirmed in three anti-PD-1 cohorts.ConclusionsOur study demonstrated that m6A regulators are closely related to TIME and the m6A score was an effective prognostic biomarker and predictive indicator for immunotherapy and chemotherapeutics. Comprehensive evaluation of m6A regulators in tumors will extend our understanding of TIME and effectively guide increasing study investigations on immunotherapy and chemotherapy strategies for HNSCC.